A Review on Finite Element Analysis of Automobile roof header Manufactured By Stamping Process - Mr. Kete Krishnaraj Shivaji; Prof. A.V. Chipade (International Journal of Innovations in Engineering Research and Technology, 2021)
In stamping operations, sheet metal is formed into a desired shape by pressing it in a hydraulic or mechanical press between suitably shaped dies. As a predominant manufacturing process, sheet metal forming has been widely used for the production of automobiles, aircraft, home appliances, beverage cans and many other industrial and commercial products. Given that the press force itself is an integral of the contact pressure distribution over the die and binder contact interfaces, it is conceivable that defects may be better identified by analyzing the contact pressure distribution directly at the tooling-work piece interface.